Enhancing Service Operations Efficiency Through Data-Driven Decision Making: Evidence from Full-Service Hotels in Southeast Asia - Dwi Savandha, Septien (Hospitality Management and Operations Journal, 2025)
The rapid expansion of the hospitality industry in Southeast Asia, driven by significant growth in international arrivals and evolving digital expectations, has heightened the need for service operations that are both efficient and data-driven. Despite advancements in digital infrastructure, many full-service hotels in the region continue to experience operational inefficiencies due to fragmented data systems, limited analytical competencies, and weak integration of data insights into managerial decision-making. This study investigates how data-driven decision making (DDDM) enhances service operations efficiency in full-service hotels across Southeast Asia by examining the extent of analytical adoption and its operational impact. A mixed-methods approach is employed, combining quantitative assessments of operational efficiency indicators with qualitative insights from hotel managers and frontline supervisors. The study integrates multiple operational dimensions labor scheduling, housekeeping performance, inventory control, guest service responsiveness, and revenue optimization to provide a holistic evaluation of DDDM effectiveness. Findings reveal that hotels implementing advanced data-driven practices achieve substantial gains in labor productivity, faster service response times, and improved resource utilization compared to hotels that rely on manual or non-integrated systems. Contextual factors such as staff analytical capability, digital infrastructure maturity, and leadership commitment significantly moderate the effectiveness of DDDM. This study contributes to hospitality management literature by offering the first integrated empirical framework linking DDDM with multidimensional service operations efficiency in Southeast Asian full-service hotels. Practical recommendations are provided to guide hotel leaders in designing data-driven strategies that improve operational performance and strengthen competitive advantage in an increasingly digital hospitality landscape.